Application of geographic information systems and global positioning systems in humanitarian emergencies : lessons learned, programme implications and future research - Kaiser, Reinhard (2003)
Documents current uses of geographic information systems (GIS) methods in humanitarian emergencies. Discusses lessons learned, programme implications and future research needs.